2016
DOI: 10.1177/0146621616676791
|View full text |Cite
|
Sign up to set email alerts
|

Item Position Effects Are Moderated by Changes in Test-Taking Effort

Abstract: This article examines the interdependency of two context effects that are known to occur regularly in large-scale assessments: item position effects and effects of test-taking effort on the probability of correctly answering an item. A microlongitudinal design was used to measure test-taking effort over the course of a large-scale assessment of 60 min. Two components of test-taking effort were investigated: initial effort and change in effort. Both components of test-taking effort significantly affected the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 33 publications
(65 reference statements)
10
68
0
1
Order By: Relevance
“…The chosen values for the linear position effect were similar to those found in the empirical study as well as the position effects reported in earlier studies (e.g., Debeer and Janssen 2013). Similarly, sample size values resemble the number of examinees from previous empirical studies on item position effects (e.g., Bulut et al 2016;Debeer and Janssen 2013;Qian 2014;Weirich et al 2016). For each crossed condition, 1000 data sets were generated.…”
Section: Simulation Designmentioning
confidence: 79%
See 4 more Smart Citations
“…The chosen values for the linear position effect were similar to those found in the empirical study as well as the position effects reported in earlier studies (e.g., Debeer and Janssen 2013). Similarly, sample size values resemble the number of examinees from previous empirical studies on item position effects (e.g., Bulut et al 2016;Debeer and Janssen 2013;Qian 2014;Weirich et al 2016). For each crossed condition, 1000 data sets were generated.…”
Section: Simulation Designmentioning
confidence: 79%
“…Item position effect, which often is viewed as a context effect in assessments (Brennan 1992;Weirich et al 2016), occurs when the difficulty or discrimination level of a test item varies depending on the location of the item on the test form. For example, the difficulty of an item can increase in later positions due to a fatigue effect or decreasing test-taking effort (Hohensinn et al 2011;Weirich et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations